Chinese Communists and Hong Kong Capitalists: 1937–1997 - Chu, C. author. aut Link
XI, 196 p.
Keywords: This book examines Chinese Communist activities in Hong Kong from the outbreak of the Sino-Japanese War in 1937 to the handover in 1997. It reveals a peculiar part of Chinese Communist history, and traces six decades of astounding united front between the Chinese Communists and the Hong Kong tycoons and upper-class business elite.